2015
DOI: 10.1073/pnas.1416463112
|View full text |Cite
|
Sign up to set email alerts
|

Endocannabinoids are conserved inhibitors of the Hedgehog pathway

Abstract: Hedgehog ligands control tissue development and homeostasis by alleviating repression of Smoothened, a seven-pass transmembrane protein. The Hedgehog receptor, Patched, is thought to regulate the availability of small lipophilic Smoothened repressors whose identity is unknown. Lipoproteins contain lipids required to repress Smoothened signaling in vivo. Here, using biochemical fractionation and lipid mass spectrometry, we identify these repressors as endocannabinoids. Endocannabinoids circulate in human and Dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
86
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(89 citation statements)
references
References 52 publications
3
86
0
Order By: Relevance
“…Other endogenous lipidic molecules proposed to directly modulate Smoothened activity include cholecalciferol (vitamin D 3 ) (46) and the endocannabinoids (47). We and others have not been able to replicate the pathway inhibition or BODIPY-cyclopamine competition reported for cholecalciferol (48).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Other endogenous lipidic molecules proposed to directly modulate Smoothened activity include cholecalciferol (vitamin D 3 ) (46) and the endocannabinoids (47). We and others have not been able to replicate the pathway inhibition or BODIPY-cyclopamine competition reported for cholecalciferol (48).…”
Section: Discussionmentioning
confidence: 56%
“…Furthermore, vitamin D synthesis depends on UV radiation, not oxidation, and cholecalciferol does not accumulate in SLOS, ruling it out as the culprit for SLOS-associated Hedgehog-related phenotypes (49). Regarding endocannabinoids, of the dozen reported to inhibit Hedgehog pathway in mammalian cells, only anandamide (N-acylethanolamide 20:4) inhibited BODIPY-cyclopamine binding to Smoothened (47). None of the compounds tested inhibited ciliary accumulation of Smoothened, and most of them including anandamide blocked activation by SAG (46).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the binding of oxysterols to the extracellular N-terminal domain of Smo is sufficient to activate the Hh pathway (Nachtergaele et al, 2013), although there is no evidence that oxysterols are endogenous Smo ligands. Furthermore, endocannabinoids have recently been identified as putative Smo inhibitors that are carried into the cell on liposomes and recruited by Ptc into endosomes, where they are thought to bind directly to Smo to inhibit its activity (Khaliullina et al, 2015). Ptc has also been implicated in regulating Smo activity by modulating phosphoinositiol levels in Drosophila; the loss of Ptc thus results in increased levels of PI4P, which in turn promotes Smo activation (Yavari et al, 2010).…”
Section: Hh Signal Transduction In Drosophilamentioning
confidence: 99%
“…Using the Drosophila wing as a model system, Suzanne Eaton's group (Max Planck Institute of Molecular Biology and Genetics, Dresden, Germany) found that very low-density lipoprotein particles in serum repress Hedgehog signaling. From fractionation experiments, they identified endocannabinoids as the active compound and showed that these bind directly to Smoothened and inhibit it; this activity is conserved from flies to humans (Khaliullina et al, 2015). This provides another beautiful example of a metabolite that plays an important signaling role, and of how metabolites and signaling components can be functionally intertwined.…”
Section: Metabolism and Metabolites Can Play Instructive Roles In Devmentioning
confidence: 99%